MicroRNA‐134 inhibits osteosarcoma angiogenesis and proliferation by targeting the VEGFA/VEGFR1 pathway. (23rd March 2018) - Zhang, Long; Lv, Zhi; Xu, Jing; Chen, Chenglong; Ge, Qiaofeng; Li, Pengcui; Wei, Dinglu; Wu, Zhuangzhuang; Sun, Xiaojuan
Abstract : Vascular endothelial growth factor (VEGF) A and vascular endothelial growth factor receptor 1 (VEGFR1) signaling is crucial for angiogenesis and progression of osteosarcoma (OS). However, the regulation of the VEGF/VEGFR1 expression is still unclear in OS. Here, we show lower levels of miRNA‐134 (miR‐134) in OS tissues and cells. Induction of miR‐134 overexpression significantly reduced the proliferation of Saos‐2 cells and their secretion of pro‐angiogenic factors, but increased the frequency of apoptotic Saos‐2 cells. Treatment with conditioned medium from the cells transfected with miR‐134 reduced the tube formation in human umbilical vein endothelial cells, which was abrogated by a combination of VEGF and conditioned medium. Furthermore, miR‐134 significantly inhibited the growth of implanted OS tumors in vivo and attenuated the VEGFA and VEGFR1 expression and angiogenesis in the tumors. In addition, higher levels of VEGFA and VEGFR1 were detected and miR‐134 inhibited the expression of VEGFA and VEGFR1 in Saos‐2 cells and OS tumors. Bioinformatic analysis indicated that the 3′‐UTR of VEGFA and VEGFR1 contained the motif for miR‐134 binding. Co‐transfection with the luciferase reporter containing the wild‐type, but not the mutant, of the 3′‐UTR of VEGFA or VEGFR1 together with miR‐134 decreased the luciferase activity in Saos‐2 cells. Finally, miR‐134 dramatically inhibited AKT activation and proliferating cell nuclear antigen expression in Saos‐2 cells. Collectively, these findings indicate that miR‐134 is a potential tumor suppressor by targeting VEGFA/VEGFR1 signaling to attenuate the progression and angiogenesis in OS. Therefore, miR‐134 may be a novel biomarker for the prognosis of OS and a target for the design of new therapies for OS. Abstract : The relative levels of miRNA‐134, vascular endothelial growth factor A (VEGFA) and VEGF receptor 1 (VEGFR1) expression were examined in osteosarcoma (OS) and non‐tumor bone tissues as well as OS cells. The data indicated that miRNA‐134 is a potential tumor suppressor by targeting VEGFA/VEGFR1 signaling to attenuate progression and angiogenesis in OS.